Enhancement in Power Conversion Efficiency of GaAs Solar Cells by Utilizing Gold Nanostar Film for Light-Trapping - Zhu, Sheng-Qing; Bian, Bin; Zhu, Yun-Feng; Yang, Jun; Zhang, Dan; Feng, Lang (Frontiers in Chemistry, 2019)
Light trapping, caused by the introduction of metallic nanoparticles, has been demonstrated to enhance photo-absorption in GaAs solar cells. In this study, we successfully synthesized gold nanostar thin film with hot spots and obtained a notable improvement of power conversion efficiency (PCE) in single-junction and three-junction high-performance GaAs solar cells by incorporating the poly (3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) layer, which enables a much stronger light trapping capability and scattering enhancement than conventional metal nanostructures. Increases of 5.2% and 3.94% in short circuit current density (Isc) were achieved for single-junction cells and three-junction cells while the enhancement in cell PCE was 3.85 and 2.50%, respectively. The relationship between the optical characteristics, the distribution density of the gold NSs and the performance of GaAs solar cells was systemically investigated.